-8(m-2)=-4

Simple and best practice solution for -8(m-2)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(m-2)=-4 equation:


Simplifying
-8(m + -2) = -4

Reorder the terms:
-8(-2 + m) = -4
(-2 * -8 + m * -8) = -4
(16 + -8m) = -4

Solving
16 + -8m = -4

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + -8m = -4 + -16

Combine like terms: 16 + -16 = 0
0 + -8m = -4 + -16
-8m = -4 + -16

Combine like terms: -4 + -16 = -20
-8m = -20

Divide each side by '-8'.
m = 2.5

Simplifying
m = 2.5

See similar equations:

| -4x(-6x-3)=12 | | .1818-x=.1x | | 28x^3-7x=0 | | 8v^2-98=0 | | (4)y-2(4)-3y+12=0 | | -6y+6=-4(2y+2) | | 2(x+1)=x-18 | | 4r^2-196=0 | | -5b+7b=8b-6 | | 3x+4=6x+1 | | -18a^2+128=0 | | (20x+3)(15x+2)(5x+11)(10x-6)= | | x+8x=3.5 | | 175-7t^2=0 | | 2r+15-6=41r+8+9 | | 8x+2-5x=3(-x-1) | | -1+(-9)+7= | | 23x+15=15x-9 | | 22x=18(x-2) | | 3x^2+2x-8=o | | 4y-2(4)-(3)y+12=0 | | 112-7t^2=0 | | 9y^2(12y+7)(4y-3)=0 | | 3(2x-1)(x-5)=0 | | 192/50= | | 9(-2)x+(2)=19(-13)x+(17) | | 5(-8)x+(-1)=20 | | (.960)x(200)/50= | | 4y-2(4)-3y+12=0 | | (.960)(200)/50= | | y^3+64= | | x^3+8= |

Equations solver categories